Microwave-assisted Pt-Co-Cr/C ternary compound preparation applied as a cathode catalyst for PEMFC - Sarakonsri T. (2014)
The present study describes the preparation of catalyst nanocomposites comprised of 20 wt.% Pt-Co-Cr (2:1:1) particles attached on the surface of carbon Vulcan XC-72R by microwave radiation; cases of carbon being chemically treated and untreated are considered. Ethylene glycol was used as the solvent and electron source for the microwave-assisted reduction reaction, whereas H2PtCl6xH2O, Co(NO3) 36H2 O and Cr(NO3)39H2 O were used as metal precursors. The C powder surface was chemically modified by stirring the C in 8N H2 O2 for 48 h. For the nanocomposite in which C was not treated, EDS analysis showed a content of 4.9 wt.% Pt and 1.2 wt.% Cr with only a trace amount of Co. Higher Pt and Cr contents were observed in the catalyst sample prepared from treated carbon (5.6% Pt and 2.2% Cr), but no Co was detected. Chromium appeared as Cr3 O4 in both samples confirmed by the XAS spectrum. The obtained phase was therefore Pt-Cr3 O4 /C for both samples. The TEM results indicated that the average particle size of Pt-Cr3O4 was 2.22 0.41 nm on treated C and 1.93 0.34 nm on untreated C. By the CV technique, it was observed that the catalytic activity of the treated carbon Pt-Cr 3O4 catalyst was not only higher than that of the untreated carbon Pt- Cr3 O4 catalyst, but also higher than that of the standard platinum catalyst. © 2010 The Royal Swedish Academy of Sciences.